LABORATORY ROUTINE FOR CHEMICAL AND ANALYTICAL PROCEDURES ON PLANT TISSUES - MARTINS, Ana Paula Lang; REISSMANN, Carlos Bruno (Scientia Agraria, 2007)
The presented text has as main purpose support students and junior researchers in their laboratory work, e. g., thesis and dissertations. This is due considering that in this case, in special, the time dispended in the laboratory is generally short and not continuous. In this sense, it is necessary to present an operational laboratory method rich in specific details that normally are not considered in the methods available in the published literature enabling the operators to be auto sufficient. The descriptions contain basic information about glassware cleaning, sample preparation and readings in different equipments. It also presents the methods of nutrient determination in a didactic way for vegetable materials, including mathematical transformations of the readings, step by step, in the different equipments to standard units. Additionally, describes methods for dry digestion – incineration; wet digestion – kjeldahl, and diluted acid extractions. For sample readings, techniques as titration, colorimetry, flame photometry, and atomic absorption spectrophotometry are described also. The bibliography cited in the text is recommended for additional readings in cases where a deeper knowledge is required. It is expected that the information, presented in the text, will be useful for the operators in conducting their analyses while utilizing the described methods.